2023
DOI: 10.1158/2767-9764.crc-22-0505
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Activation by Ubiquitin-specific Protease 6 Mediates Tumor Suppression in Ewing Sarcoma

Abstract: Ewing sarcoma (ES) is a rare and deadly pediatric bone cancer for which survival rates and treatment options have stagnated for decades. ES has not benefited from immunotherapy due to poor understanding of how its immune landscape is regulated. We recently reported that Ubiquitin-Specific Protease 6 (USP6) functions as a tumor suppressor in ES, and identified it as the first cell-intrinsic factor to modulate the ES immune tumor microenvironment (TME). USP6 induces intratumoral infiltration and activation of mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Notably, the expression of USP6 in Ewing’s sarcoma has been shown to facilitate NK cell invasion and activation, thereby enhancing their tumor cell-killing potential and underscoring the positive impact of NK cell infiltration in impeding tumor growth ( Jain et al, 2023 ). Furthermore, USP6 also stimulates the secretion of immune-related chemokines, augmenting the infiltration and activation of NK cells and additional immunocytes, significantly impeding Ewing’s sarcoma progression ( Henrich et al, 2021 ).…”
Section: Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the expression of USP6 in Ewing’s sarcoma has been shown to facilitate NK cell invasion and activation, thereby enhancing their tumor cell-killing potential and underscoring the positive impact of NK cell infiltration in impeding tumor growth ( Jain et al, 2023 ). Furthermore, USP6 also stimulates the secretion of immune-related chemokines, augmenting the infiltration and activation of NK cells and additional immunocytes, significantly impeding Ewing’s sarcoma progression ( Henrich et al, 2021 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Furthermore, studies by Jain et al observed that USP6 inhibits tumor growth in Ewing’s sarcoma by activating NK cells and inducing the expression of chemokines. USP6 increases the surface levels of NK cell activation ligands, enhancing the interaction between NK cells and Ewing’s sarcoma cells, thus augmenting the tumor-killing capability of NK cells and highlighting the significance of USP6 in regulating the TME ( Jain et al, 2023 ). Research by Pahl et al emphasized that LPS and IFN-γ-activated M1-type macrophages could inhibit osteosarcoma growth, with a similar effect observed when M1-type macrophages were activated with L-MTP-PE and IFN-γ.…”
Section: Osteosarcoma Treatmentmentioning
confidence: 99%